Changes of the quality of life and efficiency criteria of coronary artery bypass grafting in patients with stable coronary artery disease and preserved left ventricular ejection fraction - Yu.A. Borkhalenko; O.J. Zharinov; K.O. Mikhaliev; O.A. Yepanchintseva; B.M. Todurov (Кардіохірургія та інтервенційна кардіологія)
The aim – to evaluate the dynamics of quality of life (QoL) parameters and to determine objective criteria for the efficacy of coronary artery bypass grafting (CABG) in patients with stable coronary artery disease (CAD) and preserved left ventricular (LV) ejection fraction (EF) at one-year follow-up. Materials and methods. A single-center prospective study included data from a clinical, instrumental and laboratory examination of 71 patients with CAD and preserved LV systolic function (LVEF ≥ 45 %) consecutively selected for CABG. The physical tolerance was determined with 6-minute walk test; LV diastolic function parameters and the level of the brain natriuretic peptide were also analyzed. QoL was assessed using MLHFQ, SAQ and SF-36 questionnaires at 6 and 12 months after CABG. Results. Six months after CABG a significant improvement of QoL was registered by all questionnaires. With further observation (during the period from 6 to 12 months), the improvement of QoL was preserved only by MLHFQ questionnaire (p = 0.034) and the individual scales of the SF-36 questionnaire. These changes, in the first place, were determined by improvement of the functional class of angina pectoris in the majority of the examined patients (p < 0.001). The improvement of diastolic dysfunction and heart failure might also play an important role. This was reflected by a significant decrease in the level of the BNP from 115.4 (quartiles 62.0–150.6) to 52.4 (20.4–95.9) pg/ml (p < 0.001), an increase of the distance of 6-minute walk test from 260 (195–300) to 550 (415–600) m (p < 0.001), as well as improvement of some LV diastolic function parameters at 6 months. Conclusion. A most significant improvement of QoL in patients with CAD and preserved LV ejection fraction was observed during first 6 months after CABG and was combined with elimination or reduction of angina symptoms in the vast majority of revascularized patients. Favorable changes of Doppler echocardiographic indices of LV diastolic function, an increase in the distance of a 6-minute walk test and a decrease in the level of the BNP may be objective criteria for the efficiency of surgical revascularization during long-term follow-up.